Lethal punishment : lynchings and legal executions in the South - Vandiver, Margaret (Rutgers University Press, 2006)
Why did some offenses in the South end in mob lynchings while similar crimes led to legal executions? Why did still other cases have nonlethal outcomes? In this well-researched and timely book, Margaret Vandiver explores the complex relationship between these two forms of lethal punishment, challenging the assumption that executions consistently grew out of-and replaced-lynchings.